2023
DOI: 10.1161/hypertensionaha.122.20311
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Derived Vessel Density Computed From a Simplified Intravoxel Incoherent Motion Imaging Protocol in Pregnancies Complicated by Early Preeclampsia: A Novel Biomarker of Placental Dysfunction

Abstract: BACKGROUND: Early preeclampsia is associated with significant placental hypoperfusion. We explore the diagnostic value of placental diffusion-derived vessel density, a biomarker derived from diffusion-weighted magnetic resonance imaging, which measures in vivo vessel microperfusion, in the differential diagnosis of normal and early preeclampsia pregnancies. METHODS: This was a prospective study involving 29 controls and 17 singleton pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…DDVD can be interpreted as a physiological surrogate of the area of microvessels per unit tissue area, which can be conceptually converted to a surrogate of the volume of microvessels per tissue unit volume if multiple slices are integrated. The clinical usefulness of DDVD as a straightforward diffusion imaging biomarker has been recently demonstrated 14–19 . DDVD is a useful parameter for the distinguishing of livers with and without fibrosis, and livers with more severe fibrosis tend to have even lower DDVD measurements than those with milder liver fibrosis 14–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDVD can be interpreted as a physiological surrogate of the area of microvessels per unit tissue area, which can be conceptually converted to a surrogate of the volume of microvessels per tissue unit volume if multiple slices are integrated. The clinical usefulness of DDVD as a straightforward diffusion imaging biomarker has been recently demonstrated 14–19 . DDVD is a useful parameter for the distinguishing of livers with and without fibrosis, and livers with more severe fibrosis tend to have even lower DDVD measurements than those with milder liver fibrosis 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with the known physiological age‐dependent reduction in liver blood flow, which has been well documented using a variety of technical methods including histology, dye dilution, and indicator clearance. He et al 19 reported that DDVD analysis of the placenta allows excellent separation of normal and early preeclampsia pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with standard MRI intravoxel incoherent motion (IVIM) protocols, DDVD is purportedly easier to execute with less erroneous calculation and shorter scan time, proposing DDVD as a practical and valuable index of placental microperfusion. Importantly, He et al 1 found that the DDVD mean measurement inversely associates with preeclampsia pregnancy progression, is reproducible, and distinguishes early preeclampsia from normal pregnancies.…”
Section: Use Of Magnetic Resonance Imaging To Detect Placental Microv...mentioning
confidence: 99%
“…6 DDVD-based acquisition and measurements can potentially help detect early preeclampsia and placental vessel malformations and may serve as a future diagnostic imaging modality. 1 The diagnosis of preeclampsia is a compelling hurdle for early recognition and treatment of at-risk women. Blood pressure monitoring and 24-hour-urine proteinuria are essential for establishing an early diagnosis, after which further clinical and imaging studies such as Doppler Ultrasound are warranted to detect and prevent unanticipated short-and long-term complications in both mother and fetus.…”
Section: See Related Article Pp 1658-1667mentioning
confidence: 99%
“…On the other hand, earlier IVIM studies demonstrated slightly lower perfusion measures for MVI(+) HCCs or more malignment HCCs. He et al ( 17 ) reported that DDVD analysis of the placenta allowed excellent separation of normal and early preeclampsia pregnancies. More recently, Lu et al ( 18 ) reported that DDVD was significantly higher in pregnant women with placenta accreta spectrum disorders than women with normal placenta, and especially higher in patients with placenta increta and percreta.…”
Section: Introductionmentioning
confidence: 99%